Perancangan User Experience Aplikasi Pembelajaran Dasar Pemrograman Android - Valen Novandi Kanasya; Ratih Kartika Dewi; Randy Cahya Wihandika (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The Covid-19 virus pandemic was first announced in Indonesia in March 2020, forcing people to carry out limited activities. One of the activities affected by the pandemic is teaching and learning. Large-Scale Social Restrictions force schools to conduct online learning activities. Of course, this makes children's learning productivity decreases. To deal with these problems, students can learn new things to prepare for their future. One of the things that can be learned is Android programming. In the digital era, Android is very closely related to human life, therefore Android programming can be a new learning activity to increase student productivity. But of course, not all students are familiar with Android programming, therefore a good user experience is needed so that students can learn optimally. In this study, Human Centered Design (HCD) is used as an approach to develop an interactive system that aims to make the system useful and usable by users properly. This research will get the final result in the form of a high-fidelity prototype. Furthermore, the prototype that has been built will be evaluated using the heuristic evaluation method. In the implementation of this evaluation, there are three experts who act as evaluators. After the evaluation, twenty-three usability problems were found.